2021
DOI: 10.1016/j.ijrobp.2021.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Normal Tissue Complication Probability (NTCP) Prediction Model for Osteoradionecrosis of the Mandible in Patients With Head and Neck Cancer After Radiation Therapy: Large-Scale Observational Cohort

Abstract: Purpose: Osteoradionecrosis (ORN) of the mandible represents a severe, debilitating complication of radiation therapy (RT) for head and neck cancer (HNC). At present, no normal tissue complication probability (NTCP) models for risk of ORN exist. The aim of this study was to develop a multivariable clinical/dose-based NTCP model for the prediction of ORN any grade (ORN I-IV ) and grade IV (ORN IV ) after RT ( §chemotherapy) in patients with HNC.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…DVCs with moderate dose indices (V40Gy[RBE], V50Gy[RBE], and V60Gy[RBE]), instead of the DVCs with high dose indices (V70Gy[RBE] and V75Gy[RBE]), were found to have statistically significant differences between the ORN group and control group for both VMAT and PBSPT (Table 2). For VMAT, this dose volume effect at moderate doses has been reported in multiple studies related to ORN (32)(33)(34)(35)(36)(37). The derived DVCs for VMAT are consistent with the reported results (Table 3).…”
Section: Discussionsupporting
confidence: 90%
“…DVCs with moderate dose indices (V40Gy[RBE], V50Gy[RBE], and V60Gy[RBE]), instead of the DVCs with high dose indices (V70Gy[RBE] and V75Gy[RBE]), were found to have statistically significant differences between the ORN group and control group for both VMAT and PBSPT (Table 2). For VMAT, this dose volume effect at moderate doses has been reported in multiple studies related to ORN (32)(33)(34)(35)(36)(37). The derived DVCs for VMAT are consistent with the reported results (Table 3).…”
Section: Discussionsupporting
confidence: 90%
“…A subset analysis generated for the current manuscript demonstrated that 123/826 oropharyngeal cancer patients (14.9%) developed all grade ORN and 42/825 (5.1%) developed grade 4 ORN. 33 In the current cohort, Veterans who developed ORN were more likely to have pre-EBRT extractions (Table 3). No other variables reached statistical significance (Tables 1, 3).…”
Section: Discussionmentioning
confidence: 90%
“…The risk factors for ORN [12][13][14]17], such as the RT dose to the whole or to a nonanatomically defined proportion of the mandible [18][19], do not fully explain the occurrence of severe ORN events. Different mandibular topographies may range in their proclivity for the development of severe ORN.…”
Section: Discussionmentioning
confidence: 99%